Measurement of charged particle multiplicities and densities in pp collisions at √s = 7 TeV in the forward region - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; et al. (The European physical journal. C, Particles and fields, 2014)
Charged particle multiplicities are studied in proton-proton collisions in the forward region at a centre-of-mass energy of $$\sqrt{s} = 7\;$$s=7TeV with data collected by the LHCb detector. The forward spectrometer allows access to a kinematic range of $$2.0<η <4.8$$2.0<η<4.8in pseudorapidity, momenta greater than $$2\;\text{ GeV/ }c$$2GeV/cand transverse momenta greater than $$0.2\;\text{ GeV/ }c$$0.2GeV/c. The measurements are performed using events with at least one charged particle in the kinematic acceptance. The results are presented as functions of pseudorapidity and transverse momentum and are compared to predictions from several Monte Carlo event generators.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
The LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, M. De Cian, A. Di Canto, F. Dordei, S. Esen, C. Färber, M. Fontana, M. Gersabeck, L. Grillo, S. Hansmann-Menzemer, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, T. Nikodem, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, M. Vesterinen, S. Wandernoth, D. Wiedner, A. Zhelezov [und viele weitere]
Gesehen am 25.09.2020